EFEKTIVITAS QUIZIZZ MODE PAPER DALAM PENERAPAN PEMBELAJARAN TGT (TEAM GAMES TOURNAMENT) MENINGKATKAN KETERLIBATAN AKTIF PESERTA DIDIK DI SMK NEGERI 5 MAKASSAR - Syamsir Muhammad Fajri (Jurnal Education, 2025)
This study aims to enhance students' engagement and learning outcomes in the Computer Systems course for the TKJ class at SMK Negeri 5 Makassar through the implementation of the Team Games Tournament (TGT) method using Quizizz in paper mode. The research was conducted in two cycles, each consisting of two sessions for material delivery and evaluation tests. The collected data comprised students' learning outcomes, which were analyzed using qualitative descriptive analysis and percentages. The findings revealed that in the first cycle, the percentage of classical completeness reached 78.515% (categorized as sufficient), while in the second cycle, it increased to 81.121% (categorized as good), showing an improvement of 2.61%. This indicates that the application of the TGT method combined with Quizizz can enhance students' engagement in the learning process and improve their understanding of Computer Systems material, particularly on hardware and software topics. Although the improvement in learning outcomes was not substantial, the increase in classical completeness demonstrates the effectiveness of the TGT method in improving the quality of learning. This study is expected to contribute to the development of more interactive and enjoyable teaching methods at the vocational high school level.